Optimising TB investments in Belarus, Moldova, Kyrgyz Republic, Tajikistan and Uzbekistan: An allocative efficiency analysis. - Anna L Bowring; Rowan Martin-Hughes; Debra Ten Brink; Kelvin Burke; Svitlana Nidzvetska; Nisaa Wulan; Phillip Luong; Eloisa Perez-Bennetts; Nick Scott (PLOS Global Public Health)
High rates of drug-resistant tuberculosis (TB) are a barrier to achieving End TB-strategy targets in Eastern Europe and Central Asia. This analysis collates results from five country-level modelling studies to identify priorities to reduce TB burden. Allocative efficiency studies were conducted in 2023 in Belarus, Kyrgyz Republic, Moldova, Tajikistan and Uzbekistan using the Optima TB model to determine the optimised distribution of funds to maximise health outcomes with given resources. A baseline scenario of continued 2022 spending was compared to scenarios with spending optimised across prevention, screening and treatment interventions to reduce TB incidence and deaths over 2024-2030. Modelled pulmonary TB incidence ranged from 25-119 per 100,000 population, and 14 - 43% of new/relapse TB cases were drug resistant. In all countries, optimizing current spending involved: expanding shorter treatment regimens (6-9 months) for drug-resistant-TB over standard regimens (18-20 months); reducing mass screening and mandatory testing and expanding community-based active case finding focused among populations at higher TB risk; and scaling-up TB preventive treatment. It was recommended to expand contact tracing in three countries and to improve cost-effectiveness in two countries by focusing on child household contacts first. With current spending optimised, pulmonary TB incidence was projected to decrease to 19 - 95 per 100,000 population by 2030, averting 1 - 13% of new/relapse TB cases and 1 - 18% of TB-related deaths from 2024-2030 compared to continued baseline spending. In three countries, optimised allocation of 150% of current spending had minimal additional epidemic impact. There are opportunities to reallocate TB funds more cost-effectively in Eastern Europe and Central Asia, but End TB targets may remain out of reach without new and prospective interventions.